SYNTHESIS AND ANTICONVULSANT ACTIVITY OF 2-SUBSTITUTED-5-CHLOROBEN ZOXAZOLE - Ghany, Abdel-; Helby, A EL- (Biological Sciences - PJSIR, 2002)
The potassium salt(l) of 5-chlorobenzoxazole-2-thione was prepared and allowed to react with alkyl chloroacetate and alkyl 3-chloro-propiona te to afford ll _ 12 1 10 .Compound 11 2 was allowed to react with a mmonia and hydrazine hydrate to 11 afford 111 and III respecti vely. The compound 111 12 was also reacted with the appropiate aldehydes to afford com 13 pound s N _ w The potassium salt(l) was also reacted with chloro-acetanilides to afford compound s V 20_39 . Preliminary pharmacologi cal testing of some of these compounds showed that they exhibit anticonvulsant activity. The structu re of these compound s was confirmed by elemental analysis JR, 1HNMR and in some cases by MS spectral data .